Child Care Markets, Parental Labor Supply, and Child Development - Berlinski, Samuel (World Bank, Washington, DC, 2020)
This paper develops and estimates a model of supply and demand for child care. On the demand side, one- and two-parent households make consumption, labor supply, and childcare decisions. On the supply side, non-parental care providers include child care centers, paid caregivers who operate at the child’s home, and unpaid, informal care-givers. Centers make entry, price, and quality decisions under monopolistic competition. Child development is a function of the time spent with each parent and non-parental care providers; these inputs vary in impact. The model’s structural parameters are estimated using the 2003 Early Childhood Longitudinal Study, which contains information on parental employment and wages, child care choices, child development, and center quality. The model features locations that differ in size and median family income. Parameter estimates are used to evaluate multiple policies including vouchers, cash transfers, and public provision. Vouchers that can only be used in high-quality centers or that require mothers to work are particularly effective, as they deliver child development gains while increasing mothers’ labor supply, thereby limiting policies’ fiscal cost.